2017
DOI: 10.1007/s10948-017-4289-9
|View full text |Cite
|
Sign up to set email alerts
|

Published Tunneling Results of Binnig et al Interpreted as Related to Surface Superconductivity in SrTiO3

Abstract: In 1980 Binnig et al. reported tunneling measurements on Nb-doped SrTiO 3 , and interpreted their results as indicating two-band superconductivity in the bulk of SrTiO 3 . However: (1) Effective masses determined from tunneling results in the normal state by Sroubek in 1969 and 1970 are much smaller than those determined by most other methods. The much smaller masses were attributed to properties of a surface layer by the present author in 1971; (2) The only other reports of two-band superconductivity in bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…As for direct experimental evidence in favor of multiple superconducting gaps, the seminal work by Binnig et al reported two gaps in the tunneling conductance of Nb-doped STO [143], with the second gap only emerging at sufficiently high doping concentrations. Although surface effects may complicate the interpretation of this result in terms of two bulk gaps, as pointed out recently by Eagles [148], this observation is consistent with the doping evolution of the band structure of STO, as discussed by Fernandes et al [139]. More recently, measurements of the thermal conductivity κ and of the critical magnetic field H c2 have also provided strong support for the existence of multi-gap superconductivity [145,146].…”
Section: Multi-band Superconductivity and Gap Structuresupporting
confidence: 86%
“…As for direct experimental evidence in favor of multiple superconducting gaps, the seminal work by Binnig et al reported two gaps in the tunneling conductance of Nb-doped STO [143], with the second gap only emerging at sufficiently high doping concentrations. Although surface effects may complicate the interpretation of this result in terms of two bulk gaps, as pointed out recently by Eagles [148], this observation is consistent with the doping evolution of the band structure of STO, as discussed by Fernandes et al [139]. More recently, measurements of the thermal conductivity κ and of the critical magnetic field H c2 have also provided strong support for the existence of multi-gap superconductivity [145,146].…”
Section: Multi-band Superconductivity and Gap Structuresupporting
confidence: 86%
“…Although Nb-doped SrTiO 3 was initially thought to be a multiband superconductor [25], the recent data are in favor of a single-band [26][27][28] superconductor. Together these systems span a large range of disorder for which n s /n ∼ 0.6-10 −4 .…”
Section: Comparison With Experimentsmentioning
confidence: 99%